Family reunion policy for resettled refugees: Governance, challenges and impacts - Phillimore, Jenny; D'Avino, Gabriella; Strain-Fajth, Veronika; Papoutsi, Anna; Ziss, Paladia (Frontiers in Human Dynamics, 2023)
The past decade has seen renewed efforts to establish resettlement as a durable solution for refugees, both as a protection tool and a mechanism to equitably distribute them among countries. Although the right to a family life is widely recognised as a fundamental human right, whether refugees can arrive with their family or be reunited with family once resettled varies across receiving countries. Little is known about family reunion policies in countries leading the resettlement efforts, and about the impact of these policies on the lives and experiences of resettled refugees. This paper addresses this gap though a systematic scoping review of academic and policy literature on family reunion policies for resettlement refugees, and on the impact of such policy on their lives. Based on a review of 42 papers published between 2010 and 2021, we outline the policies implemented in different receiving countries to enable resettled refugees to reunite with family, documenting at the same time the challenges refugees face in the process, as well as the impact of policy on their experiences. The findings evidence a tension between the refugees’ own understanding of family and definitions of family in policy in receiving countries, which often results in family separation or reconfiguration. Additionally, the high costs and other administrative barriers, as well as long waiting times associated with family reunification, lead to delayed or denied reunion, having detrimental effects on resettled refugees’ well-being in the present and on their future prospects.